Comparative Study on the Pyrolysis Behaviors of Corn Stalk and Pine Sawdust Using TG-MS - 赵云鹏 丁曼 窦有权 樊星 王月伦 魏贤勇 (Transactions of Tianjin University, 2014)
The pyrolysis behaviors of corn stalk（CS） and pine sawdust（PS） were investigated with thermogravimetry-mass spectroscopy（TG-MS）.The peak temperature of PS was higher and the main decomposition region shifted to higher temperature compared with CS,which implied that the hemicellulose and cellulose of PS were more thermally stable than those of CS.However,the hemicellulose and cellulose of PS were more easily decomposed into gaseous products than those of CS during pyrolysis.The pyrolysis process of biomass can be described by a two-step independent first-order kinetic model.This fundamental study provides a basic insight into the biomass pyrolysis,which is beneficial for understanding the pyrolysis mechanism of biomass and developing an advanced thermal process for effective utilization of biomass.